2023
DOI: 10.1021/acs.cgd.2c01481
|View full text |Cite
|
Sign up to set email alerts
|

Critical Crystallographic Transition in Violation of Kasha’s Rule of Size-Specific ZnO Quantum Dots

Abstract: Investigation of the intrinsic relationship between crystallography and electronic properties may provide an avenue to unravel the photophysical aspects of semiconductor nanostructures. Since the 1980s, semiconducting materials at the nanoscale dimensions have been of immense scientific interest because of the unique quantum characteristics beyond a particular size limit. Prudent advances in the synthetic strategies of naked ZnO quantum dots have offered the opportunity to imbue the structure−property relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…We have investigated the excitation wavelength dependent photophysical characteristics of the colloidal dispersion of size-specific ZnO quantum dots. It has been revealed that a critical crystallographic transition correlates the excitation wavelength dependent photoluminescence shift and the violation of Kasha’s rule by these ultrasmall particles . A detailed crystallographic analysis of the size-selective ZnO particles of 2.0 ± 0.3, 3.2 ± 0.4, and 9.0 ± 1.0 nm has been shown in Figure .…”
Section: Crystallinity and Physical Propertiesmentioning
confidence: 96%
See 2 more Smart Citations
“…We have investigated the excitation wavelength dependent photophysical characteristics of the colloidal dispersion of size-specific ZnO quantum dots. It has been revealed that a critical crystallographic transition correlates the excitation wavelength dependent photoluminescence shift and the violation of Kasha’s rule by these ultrasmall particles . A detailed crystallographic analysis of the size-selective ZnO particles of 2.0 ± 0.3, 3.2 ± 0.4, and 9.0 ± 1.0 nm has been shown in Figure .…”
Section: Crystallinity and Physical Propertiesmentioning
confidence: 96%
“…(a–c) X-ray diffraction patterns, (d–f) corresponding crystalline phases, and (g–i) unit cell patterns of 2.0, 3.2, and 9.0 nm ZnO quantum dots, respectively. Reprinted with permission from ref . Copyright 2023 American Chemical Society.…”
Section: Crystallinity and Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation